Epidural Steroid Injections Are Associated with Less Improvement in the Treatment of Lumbar Spinal Stenosis: A subgroup analysis of the SPORT - Radcliff, Kris (2013)
SUMMARY OF BACKGROUND DATA: Lumbar spinal stenosis is a common incidental finding among adults over the age of 60, The use of ESI in these patients is common, although there is little evidence in the literature to demonstrate the long-term benefit of ESI in the treatment of lumbar stenosis. OBJECTIVE: The hypothesis of this study was that patients who received epidural steroid injections (ESI) during initial treatment as part of the Spine Patient Outcomes Research Trial (SPORT) would have improved clinical outcomes and a lower rate of crossover to surgery compared to patients who did not receive ESI. METHODS: Patients with lumbar spinal stenosis who received epidural steroid injections within the first three months of enrollment in SPORT (ESI) were compared to patients who did not receive epidural injections during the first three months of the study (No ESI). RESULTS: There were 69 ESI patients and 207 No-ESI patients. There were no significant differences in demographic factors, baseline clinical outcome scores, or operative details although there was a significant increase in baseline preference for nonsurgical treatment among ESI patients (62% vs. 33%, p <0.001). There was an average 26 minute increase in operative time and an increased length of stay by 0.9 days among the ESI patients who ultimately underwent surgical treatment. Averaged over four years, there was significantly less improvement in SF36 PF among surgically treated ESI patients (ESI 14.8 vs. No-ESI 22.5, p=0.025). In addition, there was also significantly less improvement among the nonsurgically treated patients in SF36 BP (ESI 7.3 vs. No-ESI 16.7, p=0.007) and SF36 PF (ESI 5.5 vs. No-ESI 15.2, p=0.009). Of the patients assigned to surgical treatment, there was a significantly increased crossover to nonsurgical treatment among patients who received an ESI (ESI 33% vs. No ESI 11%, p=0.012). Of the patients assigned to non-operative treatment, there was a significantly increased crossover to surgical treatment in the ESI patients (ESI 58% vs. No ESI 32%, p=0.003). CONCLUSION: Despite equivalent baseline status, ESI were associated with significantly less improvement at four years among all patients with spinal stenosis in SPORT. Furthermore, ESI were associated with longer duration of surgery and longer hospital stay. There was no improvement in outcome with ESI whether patients were treated surgically or nonsurgically.